THE STUDENTS’ DIFFICULTIES IN USING ENGLISH INTONATION AT BUSINESS INDONESIA MURNI SADAR POLYTECHNIC - Doris Yolanda Saragih; Hengki Mangiring P Simarmata (Politeknik Bisnis Indonesia, 2019)
This thesis is about the students’ difficulties in using English intonation. To research this subject the writer formulates the problem as follow: What are the students’ difficulties in using English intonation? It focuses on the students’ intonation in reading a dialogue, which consists of positive statement, negative statement, w-h question, and yes-no question.To answer the problem above, this thesis follows some theories, namely: Allen (1954), Haycraft (1971), Jones (1979), and Roach (2000). The research design is qualitative research. The subjects of this study are the students of Business Indonesia Murni Sadar Polytechnic, and the object is the student’s intonation. The technique of collecting data follows audio method or what is called recorded voice data. The data is analyzed by drawing the terminal contour of students’ intonation.This research discovers that there are four difficulties of students in using English intonation, namely: (1). difficulty in using correct juncture, (2). difficulty in using rising intonation for the first clause and falling intonation for the second clause in a compound sentence, (3). difficulty in using falling intonation for w-h question and rising intonation for yes-no question, and (4). difficulty in determining pitch and stress of a syllable. This research finding recommends both teacher and students to take responsibility in overcoming those difficulties. An English teacher should teach his beginner students the using of intonation and its function in every kinds of sentence. Since there is an imitation process in learning intonation, a teacher should be able to detect a falling intonation from a rising intonation in his own voice as well as in a student’s. The success of learning does not only depend on the teacher but also involves the students’ awareness to learn English.